Accuracy of ultrasonic scanning for pregnancy diagnosis in ewes of five different breeds - Malik, R S; Razzaque, M A; Al-Khozam, N M (The Indian Journal of Animal Sciences, 2012)
Linear-array real-time ultrasound scanning was used for the diagnosis of pregnancy in 167 ewes of 5 diverse breeds including fat-tailed Naeemi (N), thin-tailed Texel en and Border Leicester Merino (BLM), and semi-rat-tailed Chios (C) aild N 'BLM. Pregnancy scanniag was carried out at 45-60 days from the beginning of mating. The ewes detected as barren were rescanned after an interval of 45 days. The ewes diagnosed as pregnant at first scanning, however, were not rescanned. Accuracy of identification of pregnant ewes ranged from 66.7% to 95.5%. It was tbe highest for BLM and the lowest for N ewes. Early embryonic losses and undetected abortions may have reduced the accuracy of pregnancy diagnosis. For greater accuracy, rescanning of all the ewes at 85-100 days is recommended.